2022
DOI: 10.3389/fnagi.2022.1026688
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics studies reveal ameliorating effects of physical exercise on neurodegenerative diseases

Abstract: IntroductionNeurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, and Huntington’s disease, are heavy burdens to global health and economic development worldwide. Mounting evidence suggests that exercise, a type of non-invasive intervention, has a positive impact on the life quality of elderly with neurodegenerative diseases. X-omics are powerful tools for mapping global biochemical changes in disease and treatment.MethodThree major databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Compelling evidence suggests impaired cholesterol synthesis within the brain of AD patients [ 29 ], and intriguingly, abnormal deposition of cholesterol within tangled neurons has been observed in individuals with AD [ 6 ]. It is well known that exercise is an effective means of preventing neurodegenerative diseases [ 42 ]. Our prior investigation has elucidated that aerobic exercise has the capacity to enhance the density of cortical and hippocampal dendritic spines while concurrently mitigating the anomalous deposition of Aβ in the brain of APP/PS1 mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests impaired cholesterol synthesis within the brain of AD patients [ 29 ], and intriguingly, abnormal deposition of cholesterol within tangled neurons has been observed in individuals with AD [ 6 ]. It is well known that exercise is an effective means of preventing neurodegenerative diseases [ 42 ]. Our prior investigation has elucidated that aerobic exercise has the capacity to enhance the density of cortical and hippocampal dendritic spines while concurrently mitigating the anomalous deposition of Aβ in the brain of APP/PS1 mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The divergence of gut microbiota composition between the APP/PS1 and wild-type mice was proved to start at a young age (1-3 months), before the detection of amyloid deposition, which suggested that gut bacteria alteration could aid the early detection of AD prior to pathological evidence. 86 87 Microbial metabolites associated with AD mainly include bile acids, 88 short-chain fatty acids, 89 branchedchain amino acids, indole and pyrimidine, 90 and steroid hormones. 91 Their catabolism and synthesis are regulated by the structure and function of gut microbiota.…”
Section: Urine Testsmentioning
confidence: 99%
“…While physical and mental exercises enhance oxygen consumption and may generate the oxidative redox potential needed for proper folding of these proteins ( Figure 1 ). A prospective cohort study indicated that frequent exercises, housework-related activities, and friend/family visits were associated with a reduced risk of multiple types of dementia (Guo et al, 2022 ; Zhu et al, 2022 ).…”
Section: Lysosomal Overloading Hypothesismentioning
confidence: 99%